Hasil belajar siswa dalm pembelajaran IPS menggunakan model cooperative learning tipe think paire share - pernanda, syahti; Alwi, Elma; Sukma, Elfia (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
The purpose of this research was to improve the student learning outcomes in the Civics learning used Cooperative Learning Type Think Paire Share (TPS) in grade V elementary school. Types of this research was classroom action research with qualitative and quantitative approach. Subject of this research were teacher and students of  VA grades were 27. Research conducted in two cycles. The research procedure includes planning, implementation, observation, and reflection. The result of this research I to II cycle. (a) Lesson plan. The cycle of I was 71,4% increased to 96.4% in the II cycle. (b) Implementation, teacher’s activity of I cycle was 73,2% increased to 95,8%. Students activity of I cycle had averaged was 71,4% increased in the cycle was 96,4%. (c) The students learning outcomes in the I cycle was 74,8 increased to II cycle wa 82,7. Therefore, Cooperative Learning Type Think Pair Share appoach can increase the students learning outcomes in the Civics learning in the VA grade of elementary school of 09 In Belakang Balok, Bukittinggi Town. Keywords: Learning outcomes, IPS, Model Cooperatife learning Tipe TPS